Prognostic factors influencing overall survival in de novo oligometastatic prostate cancer patients. Issue 11 (5th June 2020) - Rii, Junryo; Sakamoto, Shinichi; Yamada, Yasutaka; Takeshita, Nobushige; Yamamoto, Satoshi; Sazuka, Tomokazu; Imamura, Yusuke; Nakamura, Kazuyoshi; Komiya, Akira; Komaru, Atsushi; Fukasawa, Satoshi; Nakatsu, Hiroomi; et al.
Abstract: Background: Oligometastatic cancer has been suggested as an intermediate state between localized disease and wide‐ranging metastases. The clinical significance of local treatment in oligometastatic prostate cancer (PCa) has been a recent topic of interest. However, standard definitions of oligometastasis are lacking. Here we studied risk factors among Japanese de novo oligometastatic patients with PCa. Methods: We retrospectively assessed clinical data from 264 patients, including locally advanced (T3 or T4N0M0) cancer, lymph‐node‐positive cancer (Tany N1M0), and cancer with ≤10 bone metastases. All patients received androgen deprivation therapy only. The number of bone metastases and clinical factors were evaluated in association with overall survival (OS) and progression‐free survival (PFS). The Mann‐Whitney U test, Cox proportional hazard models, and Kaplan‐Meier methods were used as statistical analyses. Results: Median age, PSA at baseline and OS were 74 years, 55.2 ng/mL, and 129.0 months, respectively. The cutoff for the number of bone metastases having the greatest impact on OS was ≥3 (hazard ratio [HR]: 2.67;  P  = .0001). In multivariate analysis, non‐regional lymph node (LN) metastases (HR: 2.15;  P  = .0222), ISUP grade group (GG) 5 (HR: 2.04;  P  = .0186) and ≥3 bone metastases (HR: 1.82;  P  = .0390) were independent predictors of OS. In risk classification based on these factors, OS and PFS were significantly classifiable into poor (2‐3 factors), intermediate (1 factor), and good (no factors) risk groups ( P  < .0001). Conclusion: Not only the number of bone metastases, but also non‐regional LN metastases predict OS in patients with de novo oligometastatic PCa.